Improvement of Ferroelectricity with Two-Dimensional Enwrapping Structure - Xi Wu; Ran Jiang (Crystals, 2022)
The effect of the layered InSe intercalation structure on the ferroelectric properties of HfO2 was investigated. At low crystallization temperatures, the ferroelectric phase is formed more easily. Stronger polarization and better reliability can be achieved. This result indicates that the InSe intercalation structure is promising for engineering the ferroelectric properties of HfO2.